Paran, Ishmael, and the Relationship between Judaism and Islam: A Philological Study of Bereshīt 21:21 - Maulana, Abdullah Muslich Rizal; Rachmawati, Fadhillah; Muslimah, Rachmah Intan (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This research seeks to provide a detailed analysis of the importance of Paran (פָּארָן), a desert mentioned in the Tanakh, the sacred text of Judaism, specifically in the Book of Genesis (Bereshīt/ בְּרֵאשִׁית‎) Article 21 Verse 21, through a Philological Study. Philology is a method used in the study of theology and religion to analyze the linguistic structure and meaning of religious texts. This involves comparing a text with other texts that may have different linguistic characteristics. In this particular research, three different text sources for Bereshīt 21: 21 will be examined: the Tanakh in Hebrew, the Targum in Aramaic, and the Samaritan version of the Torah in Judeo-Arabic. This research establishes that Paran now refers to a region denoting the location of the Hijaz or the Arabian plains. Several Turāts studies have revealed a clear correlation between the traditions of Judaism and Islam. This study has created possibilities for additional investigations into the predictions of Ishma'el, the offspring of Abraham, within the traditions of both religions.